2006
DOI: 10.1093/humrep/del048
|View full text |Cite
|
Sign up to set email alerts
|

Risks of miscarriage and early preterm birth in trichorionic triplet pregnancies with embryo reduction versus expectant management: new data and systematic review

Abstract: In trichorionic triplets, ER to twins is associated with an increase in the risk of subsequent miscarriage and decrease in risk of early preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
76
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 31 publications
(48 reference statements)
10
76
3
3
Order By: Relevance
“…In a previous study of trichorionic triplet (TCT) pregnancies with 3 live fetuses at 10-14 weeks' gestation, including 185 that were managed expectantly and 180 that had embryo reduction (ER) to twins, we found that ER was associated with an increase in the rate of miscarriage but a decrease in early preterm birth [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of trichorionic triplet (TCT) pregnancies with 3 live fetuses at 10-14 weeks' gestation, including 185 that were managed expectantly and 180 that had embryo reduction (ER) to twins, we found that ER was associated with an increase in the rate of miscarriage but a decrease in early preterm birth [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…This constellation is found in approximately one-fourth of our triplet and quadruplet population at 11-14 weeks. Previous studies reported between 11 and 24 % of triplets containing monochorionic placentas [10,11]. The prevalence of monochorionic pairs in spontaneously conceived triplets is between 40 and 50 % [9], while it is only 5-10 % after assisted conception [5].…”
Section: Discussionmentioning
confidence: 90%
“…Management options and survival of triplets are frequently discussed [2,11,12]. It is generally accepted that selective reduction in higher-order multiples has a positive impact on gestational length but may increase the risk of miscarriage [13].…”
Section: Introductionmentioning
confidence: 99%
“…Selective embryo reduction in the first trimester also improves perinatal outcomes in triplets [20,21] , decreasing rates of preterm delivery before 32 weeks (RR = 0.37, 95% CI = 0.27-0.51) [21] . On the other hand, embryo reduction is associated with an increased risk of miscarriage (RR = 1.83, 95% CI = 1.08-3.16) [21] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, embryo reduction is associated with an increased risk of miscarriage (RR = 1.83, 95% CI = 1.08-3.16) [21] . Currently, there is not enough evidence to recommend embryo reduction because of the lack of randomized trials [22] .…”
Section: Discussionmentioning
confidence: 99%